Small bowel obstruction as a result of an obturator hernia: a rare cause and a challenging diagnosis. Issue 7 (3rd July 2018) - Pavlidis, Efstathios; Kosmidis, Christoforos; Sapalidis, Konstantinos; Tsakalidis, Alexandros; Giannakidis, Dimitrios; Rafailidis, Vasileios; Koimtzis, Georgios; Kesisoglou, Isaak
Abstract: Obturator hernias are exceedingly rare in surgical routine, constituting 0.073% of all intra-abdominal hernias in the West and 1% in the far East. Commonly known as 'little old lady's hernia', obturator hernias are usually seen in frail, octogenarian multiparous women. This case report discusses an 85-year-old female who had symptoms of acute bowel obstruction; thanks to high degree of clinical suspicion and aided by a computed tomography (CT) of abdomen and pelvis, an incarcerated right obturator hernia was diagnosed preoperatively and treated successfully. Obturator hernia is a rare condition associated with a high rate of morbidity and mortality. CT scan is the most accurate imaging method for pre-operative diagnosis. Early diagnosis and surgical intervention are fundamentals to lead to better outcomes for the patients.